Backpack Bootstrapping: Social Entrepreneurship Education Through Experiential Learning. Issue 2 (4th May 2021) - Thomsen, Bastian; Muurlink, Olav; Best, Talitha
Abstract: This paper addresses a gap in the literature regarding social entrepreneurship education through an exploratory study that leverages three separate, but distinct experiential learning projects. Students were randomly assigned into three separate groups: action-research, service learning, and a 'traditional' new social enterprise venture. All three approaches fostered student development and social entrepreneurial skill building. However, experiential learning (action research and service-learning) placed a greater emphasis on student comprehension of the subject matter in relation to the weight of responsibility they experienced by partnering with third-party organisations outside the classroom, compared to the traditional new venture approach. The findings indicate that experiential learning is an optimal conduit to student maturity when coupled with self-reflection and class discussion. The term backpack bootstrapping is introduced to illustrate how students rapidly learn by taking on a real but manageable weight of responsibility they assign to themselves. This study is original for its approach to incorporating student voices to gauge how their learning may be enhanced to improve social entrepreneurship education. Although it is an exploratory study and limited in its scope (26 students over one semester), it provides a basis for further research using experiential learning models in social entrepreneurship education.